2008
DOI: 10.1080/08959280801917727
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Self-Efficacy, Pay-for-Performance Perceptions, and Pay Satisfaction: A Korean Examination

Abstract: This study is an effort to extend our understanding of the antecedents of pay satisfaction, particularly in multiple South Korean firms. We first examine the impact of self-efficacy on overall pay satisfaction and three of its subdimensions: satisfaction with pay level, satisfaction with benefits, and satisfaction with pay structure/administration. Next, we assess the moderating effects of pay-for-performance perceptions on the relationship between self-efficacy and pay satisfaction. Results from 256 employees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 58 publications
1
23
0
1
Order By: Relevance
“…SCCT and research on performance perceptions suggest indirect effects of objective performance on self-efficacy via (subjective) performance perceptions (Kim et al, 2008;Lent et al, 1994). The results of the indirect effects analyses in our study provide support for this reasoning within the context of career development.…”
Section: Positive Feedback Loop Between Occupational Self-efficacy Ansupporting
confidence: 77%
See 1 more Smart Citation
“…SCCT and research on performance perceptions suggest indirect effects of objective performance on self-efficacy via (subjective) performance perceptions (Kim et al, 2008;Lent et al, 1994). The results of the indirect effects analyses in our study provide support for this reasoning within the context of career development.…”
Section: Positive Feedback Loop Between Occupational Self-efficacy Ansupporting
confidence: 77%
“…The provision of support to others may be experienced as mastery, or more generally as success after occupational re-entry. Furthermore, some other studies showed that individual performance perceptions are related to self-efficacy beliefs (Kim, Mone, & Kim, 2008;Tschannen-Moran & Hoy, 2007). In sum, subjective career success should therefore positively affect occupational self-efficacy within a positive feedback loop.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…Considering the debate between generalized self-efficacy and specific self-efficacy(S. Kim, Mone, & Kim, 2008), this study captured self-efficacy in the driving context. Following Tronsmoen (2008) practice, driving self-efficacy in this study was measured with a 14-item scale, seven items for generalized self-efficacy and specific self-efficacy respectively, indicating the belief in their ability to succeed in certain driving occasions.…”
Section: Driving Self-efficacymentioning
confidence: 99%
“…Gist and Mitchell (, p. 186) state that it ‘influences individual choices, goals, emotional reactions, effort, coping, and persistence.’ A meta‐analysis has found a robust relationship between self‐efficacy and work‐related performance (Stajkovic & Luthans, ). Additionally, self‐efficacy has been related to other important outcomes, such as goal level (Brown, Cron, & Slocum, ), salesforce selling intentions of a new product (Fu, Richards, Hughes, & Jones, ), service quality (Hartline & Ferrell, ), role innovation (Nicholson & Imaizumi, ), job satisfaction (Arnold, Flaherty, Voss, & Mowen, ), perceived behavioral control related to using job‐search Web sites (Lin, ), pay satisfaction (Kim, Mone, & Kim, ), and team member proactivity and proficiency (Strauss, Griffin, & Rafferty, ). It is thus an important construct to predict and improve work performance (Gist & Mitchell, ).…”
Section: Introductionmentioning
confidence: 99%